2006
DOI: 10.1007/s11738-006-0029-7
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellic acid improves water deficit tolerance in maize plants

Abstract: Ab stractThe com bi na tion ef fects of wa ter stress and gibberellic acid (GA 3 ) on phys i o log i cal at trib utes and nu tri tional sta tus of maize (Zea mays L. cv., DK 647 F1 ) were stud ied in a pot exper i ment. Maize plants were grown in the con trol (well watered WW) and wa ter stress sub jected to treated both wa ter stress and two con cen tra tions of gibberellic acid (GA 3 25 mg·L -1 , 50 mg·L -1 ). WS was im posed by main tain ing the moisture level equiv a lent to 50 % pot ca pac ity whereas the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Various growth parameters, like LAI, LAD, NAR, and TDM, were reduced under drought stress and without growth enhancer. It has been previously reported that gibberellic acid is helpful in enhancing growth of wheat, maize, and tomato under water stress conditions (Kaya et al, 2006;Maggio et al, 2010). Improved growth might be due to optimum uptake of various nutrients, as gibberellic acid found to play an important role in enhancing the N, P, K, content (Soad, 2005;Sayed, 2001) (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Various growth parameters, like LAI, LAD, NAR, and TDM, were reduced under drought stress and without growth enhancer. It has been previously reported that gibberellic acid is helpful in enhancing growth of wheat, maize, and tomato under water stress conditions (Kaya et al, 2006;Maggio et al, 2010). Improved growth might be due to optimum uptake of various nutrients, as gibberellic acid found to play an important role in enhancing the N, P, K, content (Soad, 2005;Sayed, 2001) (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…AsA supplement, implying that this treatment can alleviate the deleterious effects of salt stress. Gibberellic acid has been reported to be helpful in enhancing growth of wheat, maize and tomato under saline conditions (Ashraf et al 2002;Kaya et al 2006;Maggio et al 2010). Salt stress was strong enough to inhibit plant growth due to reduction in gibberellin production (Kaya et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Gibberellic acid has been reported to be helpful in enhancing growth of wheat, maize and tomato under saline conditions (Ashraf et al 2002;Kaya et al 2006;Maggio et al 2010). Salt stress was strong enough to inhibit plant growth due to reduction in gibberellin production (Kaya et al 2006). Table 5 Effects of sodium chloride, gibberellic acid and ascorbic acid on content of sodium in root (Na ROOT ) and shoot (Na SHOOT ), and potassium in root (K ROOT ) and shoot (K SHOOT ) in Phaseolus vulgaris L. Therefore, addition of exogenous gibberellic acid might increase seedling growth by enhancing the content of endogenous gibberellin as that mentioned by Rodriguez et al (2006).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the exogenous application of GA 3 as mitigating, has enabled the plants retain a larger amount of water in the leaves, favoring the growth process, mainly related to elongation and cell division, even under stress conditions (Kaya et al, 2006;Taiz and Zeiger, 2013). However, so that the plants can respond to the stimulus applying GA 3 , studies are needed to elucidate the application form and the correct dose of phytohormone for each species.…”
Section: Introductionmentioning
confidence: 99%